Factors associated with occupational therapy students’ preferences for courses and teaching - Tore Bonsaksen (Cogent Education, 2018)
Background: Students’ preferences for teaching have been associated with their own approaches to studying. However, whether teaching preferences are associated with a set of student characteristics is yet unknown. Aim: To investigate whether sociodemographic, education-related and personal factors were associated with preferences for teaching among Norwegian occupational therapy students. Methods: One hundred and forty-six students (mean age 23.7 years, 78.8% women) participated in the study. Self-report questionnaires were employed, including the Approaches and Study Skills Inventory for Students, the Rosenberg Self-Esteem Scale, and the General Self-Efficacy Scale. Differences between student cohorts were analyzed with one-way analyses of variance and χ2-tests, whereas factors associated with the students’ teaching preferences were analyzed with linear regression models. Results: Overall, the students preferred teaching oriented toward “transmitting information” over teaching oriented toward “supporting understanding”. Higher age, higher levels of general self-efficacy and spending more time on independent study were associated with having a stronger preference for the “supporting understanding” teaching type. Conclusions: Compared to their counterparts, students of higher age, who study more independently, and who have higher general self-efficacy are more inclined to prefer teaching that supports understanding, which is compatible with the expectations in higher education institutions.